Consolidating behavioural economics and rational choice theory: Insights from inequality research - Klarizze Anne Martin Puzon; Rachel M. Gisselquist (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Using illustrations from research on inequality, this paper offers evidence on the strengths of 'behavioural synthesis', i.e. the reconciliation between neoclassical and behavioural economics. We compare how theoretical models of absolute and relative inequality have evolved from assumptions of income maximization to status-seeking competition, and to altruism. We emphasize the relevance of experiments in testing competing theories and mitigating empirical shortcomings. We conclude that methodological pluralism, i.e. scientific integration, is necessary when it comes to understanding inequality and propose strategies on how it can be done.
Keywords: C90; B41; D30; D91; 330; inequality; behavioural economics; scientific integration; pluralism